Caries Severity of Primary Teeth among Kindergarten Children in Mosul City Using International Caries Detection and Assessment System - Saher S Gasgoos (University of Mosul, College of Dentistry, 2011)
Aims: To assess the severity of dental caries and its relation to risk factors such as parents' education, income level, demographic variables, dental attendance....etc using the International Caries Detection and Assessment System on the primary teeth of kindergarten children in Mosul City Center. Materials and Methods: The study sample was randomly selected from (8) kindergarten in Mosul City. The sample size was (219) child (120 males and 99 females), their ages ranged between (3-6) years. Risk factors considered on caries severity included parent's income level, parent's education, visiting the dentist, types of dental treatment performed and brushing behavior. dmft and the percentage of caries free students were also considered. Caries severity was measured using International Caries Detection and Assessment System. Results: These factors have an effect to increase or decrease caries severity either significantly or not significantly. Conclusion: considerable efforts are required in prevention of dental caries in these children. There is a lot of untreated caries, which needs immediate attention.